LOCAL WISDOM VALUES OF JAKA TARUB AND BIDADARI SITES IN EAST JAVA ON ENVIRONMENTAL ECOLOGY SUSTAINABILITY - Alrianingrum, Septina (Universitas Negeri Surabaya, 2025)
The legend of Jaka Tarub, which has been known as popular folklore, actually has a deep ecological content from respect for water sources and forests to ethics of interacting with nature. The story of Jaka Tarub and Bidadari Nawangwulan occupies an important position as an oral tradition that conveys moral, social, and ecological values relevant to modern life. This study aims to analyze the ecological meanings embedded in the Jaka Tarub narrative and examine its relevance as a source of environmental learning in social studies education. This research employs a qualitative descriptive approach using literature review, field observations, and in-depth interviews with communities around sites associated with the Jaka Tarub legend. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that the story reflects strong environmental ethics, including the sacralization of water sources, forest conservation, food security, and harmonious relationships between humans and nature. These values represent traditional ecological knowledge that supports environmental sustainability and socio-cultural resilience. The study concludes that integrating local wisdom from the Jaka Tarub legend into social studies learning can strengthen environmental awareness, cultural identity, and sustainable attitudes in responding to contemporary ecological challenges